Integration of ICT in Islamic Education in Junior High Schools - Iskandar, M Yakub; Hendri, Nofri; Asril, Zainal; Irfan, Muhammad; Efendi, Efendi; Alatise, Toyosi (Islamic Studies and Development Center (ISDC) Universitas Negeri Padang, 2024)
This study was motivated by the teaching and learning process of Islamic Religious Education and Ethics in one of the junior high school classes in Indonesia, which still uses the lecture method and only uses textbooks as teaching media. As a result, students do not understand and are not actively involved in the learning process. Teachers have not fully optimized the available learning media, including interactive multimedia, and there are limitations in teachers' ability to develop learning media, so that learning becomes interesting and students can understand the material. This study aims to develop valid and practical interactive multimedia products for Islamic Religious Education and Ethics lessons. This research is a research and development (R&D) study using the development model proposed by Borg & Gall. The development procedure in this study consists of five stages, namely: i) planning, ii) initial product development, iii) product validation, iv) product testing, and v) final product. Product validity testing was conducted by three validators, namely one subject matter expert and two media experts. Product testing was conducted on 20 high school students with the aim of determining the practicality of the developed product. The data collection tool was a questionnaire. The results of the product validity test by subject matter experts obtained an average score of 4.71 in the valid category, while the media aspect obtained an average score of 4.69 in the valid category. The results of the practicality test analysis obtained an average score of 4.66, placing the interactive multimedia product in the “good or practical” category. Based on the validity and practicality test results, it can be concluded that the interactive multimedia produced is feasible for use in Islamic Religious Education and Ethics lessons at the junior high school level in Indonesia.